Pollen Studies on Vida laba L. I, Germination Medium and Incubation Duration and Temperature - Lim, E. S. (1979)
The optimum culture conditions for V. faba pollen in vitro were determined using factorial combinations of agar and sucrose concentrations with various incubation durations and temperatures. Maximum pollen germination and the growth was obtained using a culture medium c0nsisting of 2% agar and 25% sucrose and incubating for 2 hours at 25°C. The bursting of pollen grains and tubes were minimum under these condition